Messenger RNA‐ Versus Retrovirus‐Based Induced Pluripotent Stem Cell Reprogramming Strategies: Analysis of Genomic Integrity. (15th April 2014) - Steichen, Clara; Luce, Eléanor; Maluenda, Jérôme; Tosca, Lucie; Moreno-Gimeno, Inmaculada; Desterke, Christophe; Dianat, Noushin; Goulinet-Mainot, Sylvie; Awan-Toor, Sarah; Burks, Deborah; Marie, Joëlle; Weber, Anne; et al.
Abstract : Differentiation studies indicated that mRNA‐derived induced pluripotent stem cells (iPSCs) differentiated efficiently into hepatoblasts and that these cells did not load additional copy number variations during differentiation. The integration‐free hepatoblasts that were generated constitute a new tool for the study of diseased hepatocytes derived from patients' iPSCs and their use in the context of stem cell‐derived hepatocyte transplantation. Abstract : The use of synthetic messenger RNAs to generate human induced pluripotent stem cells (iPSCs) is particularly appealing for potential regenerative medicine applications, because it overcomes the common drawbacks of DNA‐based or virus‐based reprogramming strategies, including transgene integration in particular. We compared the genomic integrity of mRNA‐derived iPSCs with that of retrovirus‐derived iPSCs generated in strictly comparable conditions, by single‐nucleotide polymorphism (SNP) and copy number variation (CNV) analyses. We showed that mRNA‐derived iPSCs do not differ significantly from the parental fibroblasts in SNP analysis, whereas retrovirus‐derived iPSCs do. We found that the number of CNVs seemed independent of the reprogramming method, instead appearing to be clone‐dependent. Furthermore, differentiation studies indicated that mRNA‐derived iPSCs differentiated efficiently into hepatoblasts and that these cells did not load additional CNVs during differentiation. The integration‐free hepatoblasts that were generated constitute a new tool for the study of diseased hepatocytes derived from patients' iPSCs and their use in the context of stem cell‐derived hepatocyte transplantation. Our findings also highlight the need to conduct careful studies on genome integrity for the selection of iPSC lines before using them for further applications.